Uneven but conservative pacing is associated with performance during uphill and downhill running - Johnson, A. J.; Schmitt, E. E.; French, J. R.; Johnson, E. C. (International Journal of Sports Physiology and Performance, 2022)
Purpose: To investigate the relationship between pacing strategy and performance during uphill and downhill running—specifically, what distribution of energy corresponds to faster race finish times between and among participants.